2000
DOI: 10.1081/ddc-100100324
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of Itraconazole in Rats and Rabbits After Administration of Tablets Containing Solid Dispersion Particles

Abstract: A tablet dosage form containing solid dispersions of itraconazole (Asd tablets) was prepared by using the spray-drying and wet granulation methods. The dissolution rate of itraconazole from Asd tablets was fast, with more than 90% released within 10 min, compared to less than 20% for a marketed product, Sporanox capsules. The oral absorption of itraconazole from Asd tablets was determined in rats and rabbits and was compared with that for Sporanox capsules. In the rat, there was no difference between the Asd t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(28 citation statements)
references
References 13 publications
2
25
1
Order By: Relevance
“…The solid dispersion gave higher plasma concentrations of drug compared to itraconazole power (not detected). Our results suggested that the higher initial plasma concentrations of itraconazole were due to the increased dissolution rate of drug in the solid (Yoo et al, 2000;Li et al, 2008). However, the total plasma concentrations of itraconazole in solid dispersion were not significantly different from those in commercial product in rats.…”
Section: Dissolutioncontrasting
confidence: 75%
“…The solid dispersion gave higher plasma concentrations of drug compared to itraconazole power (not detected). Our results suggested that the higher initial plasma concentrations of itraconazole were due to the increased dissolution rate of drug in the solid (Yoo et al, 2000;Li et al, 2008). However, the total plasma concentrations of itraconazole in solid dispersion were not significantly different from those in commercial product in rats.…”
Section: Dissolutioncontrasting
confidence: 75%
“…7. A linear relationship was established between the peak area and Itraconazole in the concentration range of 0.1 and 20 μg mL The prepared mucoadhesive formulation exhibited C max 1898±75.23 ng/ml which is comparable to reported value of standard formulation sporanox (16), t max of the formulation was 2 h. The plasma concentrations of itraconazole were followed for 48 h and the AUC was observed to be 28,604.9 ng h/ml (Fig. 8), which is slightly better as compared to reported value for sporanox (23,382.2±6,326).…”
Section: In-vivo Studysupporting
confidence: 61%
“…In vivo evaluation was carried out in rabbits of the optimized formulation of itraconazole tablets to establish the bioavailability of the formulation (16).…”
Section: In Vivo Study Of Optimized Formulationmentioning
confidence: 99%
“…Thus, in spite of the high antifungal activity, the bioavailability of unformulated crystalline ITZ is extremely low (Jung et al 1999;Verreck et al 2003). In order to enhance its solubility and dissolution rate and thereby bioavailability, various formulations have been developed and ample literature is available (Miyake et al 1999;Peeters et al 2002;Jung et al 1999;Yoo et al 2000;Verreck et al 2003;Lee et al 2005;Janssens et al 2008;Hassan et al 2004;Nakarani et al 2010;Uch et al 1999;Gilis et al 1997).…”
Section: Introductionmentioning
confidence: 95%